Identification of ARHGEF38, NETO2, GOLM1, and SAPCD2 Associated With Prostate Cancer Progression by Bioinformatic Analysis and Experimental Validation - Sun, Zhuolun; Mao, Yunhua; Zhang, Xu; Lu, Shuo; Wang, Hua; Zhang, Chi; Xiao, Chutian; Cao, Yinghao; Qing, Yunhao; Wang, Yu; Li, Ke (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer (PCa) represents one of the most prevalent types of cancers and brings heavy burdens in men. The pathogenic mechanisms of PCa still need further investigation. The aim of this study was to construct an effective signature to predict the prognosis of PCa patients and identify the biofunctions of signature-related genes. Firstly, we screened differentially expressed genes (DEGs) between PCa and normal control tissues in The Cancer Genome Atlas (TCGA) and GSE46602 datasets, and carried out weighted gene co-expression network analysis (WGCNA) to determine gene modules correlated with tumor. In total, 124 differential co-expression genes were retained. Additionally, five genes (ARHGEF38, NETO2, PRSS21, GOLM1, and SAPCD2) were identified to develop the prognostic signature based on the TCGA dataset. The five-gene risk score was verified as an independent prognostic indicator through multivariate Cox regression analyses. The expression of the five genes involved in signature was detected in Gene Expression Omnibus (GEO), GEPIA, and Oncomine databases. In addition, we referred to DiseaseMeth 2.0 and MEXPRESS and found that abnormal methylation patterns might be a potential mechanism for these five genes differentially expressed in PCa. Finally, we observed that the five genes except PRSS21 were highly expressed in tumor samples and PCa cells. The functional experiments revealed that silencing of ARHGEF38, NETO2, GOLM1, and SAPCD2 suppressed the proliferation, migration, invasiveness of PCa cells. In summary, this prognostic signature had significant clinical significance for treatment planning and prognostic evaluation of patients with PCa. ARHGEF38, NETO2, GOLM1, and SAPCD2 may serve as oncogenes in PCa.